A case study on performance evaluation of power tiller between slopes 3º - 5 º on dry paddy field / Muhammad Nazmi Mohd Raffi - Mohd Raffi, Muhammad Nazmi (Faculty of Plantation and Agrotechnology, 2016)
A study was conducted in UiTM Jasin Share Farm to test the relationship between speed and plowing depth and fuel and effective field capacity using two-wheel tractor (model S 120). Data collected includes time taken during plowing, total time, fuel consumption and plowing depth. The average speed recorded for each plot is 0.884,0.988,0.945, 1.022 and 0.910 (km/hr), respectively. Mean for plowing depth for each plot (from 20 samples per plot), was 7.46, 7.38, 7.4, 7.34 and 7.42 cm respectively. Effective field capacity recorded 0.0422,0.0450,0.0439, 0.0458 and 0.0427 (km/hr). Data recorded show that more speed will give less plowing depth. Fuel consumption recorded 1.39, 1.42, 1.39, 1.45, and 1.38 (l1hr). Fuel cost recorded 2.1548,2.2012,2.1542,2.2477 and 2.1391 (RM/hr).